Republican populist : Spiro Agnew and the origins of Donald Trump's America - Holden, Charles J.; Messitte, Zach P., 1968-; Podair, Jerald E., 1953- (University of Virginia Press, 2019)
"This book examines Spiro Agnew as a politician who, under the tutelage of William Safire, Pat Buchanan, Kevin Phillips, and Richard Nixon, became a spokesman for a right-wing populism that enabled Republicans to wrest the title "the people's party," from the Democrats. Agnew provides a useful point of entry to understand the ascendancy of anti-elitist, populist Republican conservatism of figures like Goldwater, Agnew, Buchanan, and Reagan, and the larger transformation of the Republican Party rooted in anti-New Deal conservatism of the 1930s"--